Journal of western archives - Utah State University ([Utah State University], 2010)
Focuses on contemporary issues and developments in the archival and curatorial fields, particularly as they affect Western archives and manuscript repositories. Submissions that provide insights on how technological changes have affected archival theory and practice are welcome, as are those that consider collaborative efforts and projects between different cultural heritage institutions. The history of archives/special collections and the development of the archival and curatorial professions in the western United States are also of particular interest.
Keywords: Archives : West (U.S.) : Periodicals; Archives : Technological innovations : West (U.S.) : Periodicals; Archival resources; Archives; Archives : Technological innovations; West (U.S.) : Archival resources : Periodicals; West United States; Archives, Ancient Documents & Seals